A design of waveguide elliptic filter based on resonant diaphragms with a complex aperture. (1st October 2018) - Zemlyakov, Viacheslav; Krutiev, Sergey; Tyaglov, Mikhail; Shevchenko, Valery
Summary: A novel approach to the synthesis of waveguide band‐pass elliptic filters on the transverse metal resonant diaphragms with the complex aperture is proposed. The aperture of the diaphragm is considered to be a rectangular window with two L‐shaped metal ridges. For the complex conductivity of the diaphragm, we solve the corresponding electrodynamic problem. We also construct and investigate an equivalent circuit of the resonant diaphragm containing a series‐parallel LC circuit. The geometry of the diaphragm aperture is found to be corresponding to the parameters of the equivalent circuit. We construct a third‐order elliptic filter and provide a computer simulation of the diaphragms satisfying the amplitude‐frequency characteristics of its resonators. We show that some resonators can be located on one complex resonant diaphragm, which then reduces the length of the filter. The band‐pass filter for a rectangular waveguide WR137 is developed and manufactured. The central frequency of the filter is 6.6 GHz, the passband width 7.5 % with return loss of −20 dB, and the total length is 34 mm. Abstract : A novel approach to the synthesis of waveguide band‐pass elliptic filters on the transverse metal resonant diaphragms with the complex aperture is proposed where the aperture of the diaphragm is a rectangular window with two L‐shaped metal ridges. The third‐order band‐pass elliptic filter for a rectangular waveguide WR137 with a bandwidth 7.5 %, and a length of 34 mm is developed and manufactured.